Value addition of pomegranate seed oil: Effect of seed pretreatment methods on yield, quality attributes and functional properties - Kaseke, Tafadzwa (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhDFoodSc)--Stellenbosch University, 2021.